2023
DOI: 10.1038/s41598-023-48065-w
|View full text |Cite
|
Sign up to set email alerts
|

Synecology of Lagoecia cuminoides L. in Italy and evaluation of functional compounds presence in its water or hydroalcoholic extracts

Enrico V. Perrino,
Zuhair N. A. Mahmoud,
Francesca Valerio
et al.

Abstract: Lagoecia cuminoides L. is a very rare and threatened taxon in Italy, never studied before for its ecology and potential use for human consumption. Furthermore, few data are available on the biological activities of its metabolites. A phytosociological study was carried out in the only two Italian sites, and its state of conservation was also evaluated according to the IUCN (International Union for Conservation of Nature) protocol. The collected plant material was used to make two types of extracts: hot water i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…A single corridor restoration can no longer satisfy the protection and management needs of the Ephedra species. On this basis, as suggested for other threatened rare plant species with a very restricted range or very small populations [ 77 ], protection is fundamental. In our case, this can be carried out by taking measures such as establishing nature reserves for special protection and management, maintaining the integrity of the habitat, and avoiding further fragmentation of the habitat caused by human factors [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…A single corridor restoration can no longer satisfy the protection and management needs of the Ephedra species. On this basis, as suggested for other threatened rare plant species with a very restricted range or very small populations [ 77 ], protection is fundamental. In our case, this can be carried out by taking measures such as establishing nature reserves for special protection and management, maintaining the integrity of the habitat, and avoiding further fragmentation of the habitat caused by human factors [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Developing and strengthening conservation genetic studies to assess or protect genetic diversity has been wildly suggested as a good strategy to assure the sustainable use of wild resources, especially endangered plants ( Liu et al., 2020 ; Garcia-Jacas et al., 2021 ; Accogli et al., 2023 ; Perrino et al., 2023 ). The precise evaluations of genetic diversity and population genetic structure could assist to compile knowledge-based and efficient protection programs ( Liu et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The complex interplay between genes and environments shapes the population structures and phenotypes of plant species ( Li et al., 2021 ). Changes in the environment can significantly impact the quality of medicinal herbs ( Yang et al., 2018 ; Perrino et al., 2023 ). For instance, environmental change can influence the medicinal properties of medicinal herbs by affecting gene expression and consequently altering the abundances of secondary metabolites ( Blanquart et al., 2013 ).…”
Section: Introductionmentioning
confidence: 99%